Optimization of consortia Chlorella vulgaris and Nannochloropsis oculata in remediation of palm oil mill effluent - Amalia Andin Vita; Soeprobowati Tri Retnaningsih; Christwardana Marcelinus (E3S Web of Conferences)
The palm oil industry in Indonesia produces abundant production waste, including solid, liquid, and gas forms. The management of palm oil mill wastewater (POME) is still not optimal. The purpose of this study was to analyze the remediation of palm oil wastewater using a consortium of Chlorella vulgaris and Nannochloropsis oculata. The study analyzed (COD), total suspended solids (TSS), pH, salinity, and microalgae cell density at various POME concentrations (0%, 25%, 50%, 75%, and 100%). The results showed that a POME concentration of 50% produced the highest total microalgae cell density at 774 x 10³ cells/mL. A significant decrease in salinity (18%) was observed at a POME concentration of 75% with a microalgae consortium. The effective pH for the microalgae consortium is between 8-9. In addition, the microalgae consortium effectively reduced COD by 70.3% and reduced TSS by 46.74%. Therefore, the consortium of Chlorella vulgaris and Nannochloropsis oculata has potential in the remediation of POME waste.